The role of parents and society in value education and civic education - Ravita Mega Saputri; Marzuki Marzuki (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
The role of people and society is very important in children's growth, because with the education provided by parents and the community to instill value education and civic education. This paper is a qualitative research using literature review method, the data is then analyzed and studied inductively. The results of this study indicate that the role of people as first educators in the family environment has an influence on children's personality development and supports children's education. Meanwhile, the role of the community in value education and civic education is its role as the organizer and implementation of quality education in everyday life in society. However, an obstacle is an obstacle in instilling value education and citizenship education both in the family or community environment that does not support the formation of a value. The efforts of parents and society in instilling value education and civic education properly for children by realizing a culture of mutual cooperation, not littering, and reprimanding children for taking bad actions.